2019
DOI: 10.1111/jerd.12489
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repetitive firings on the color of an alumina ceramic system with varying ceramic shade and thickness

Abstract: Objective The color of all‐ceramic restorations is one of the main criteria to achieve esthetical success. Many factors such as ceramic thickness, condensation techniques, firing temperature, and numbers can affect the final color of restoration. The purpose of this study was to investigate the color changes in alumina‐based ceramic system according to ceramic shade and thickness during the multiple firings. Materials and Methods Sixty disc‐shaped specimens with two different veneering porcelain shades (A1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Additionally, Barghi 12 observed that there was a slight change in color with the increase in the number of firings, but this difference was dependent on the type of porcelain used; moreover, the color remained stable after five firings. Studies which obtained alteration in color parameters emphasized that they were still within acceptable levels 3,7,9,13,31–36 . A study that evaluated lithium disilicate after seven firings noticed a small change in color (ΔE = 1.61) and related it to the highest homogeneity of the CAD/CAM material 3 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Barghi 12 observed that there was a slight change in color with the increase in the number of firings, but this difference was dependent on the type of porcelain used; moreover, the color remained stable after five firings. Studies which obtained alteration in color parameters emphasized that they were still within acceptable levels 3,7,9,13,31–36 . A study that evaluated lithium disilicate after seven firings noticed a small change in color (ΔE = 1.61) and related it to the highest homogeneity of the CAD/CAM material 3 …”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant difference of the values of the color coordinates, ∆E values of ∆E 1–2 = 2.04 and ∆E 1–3 = 2.14 after the second and third pressing cycles, respectively, indicate the acceptable color stability of the repressed materials. In the dental literature, it is widely acknowledged that ΔE values below 2.7–3.3 are clinically acceptable [ 27 , 28 , 29 ]. The ΔE values of the current study were lower than those reported by ElNaggar et al [ 30 ], who reported a ΔE value of 3.78.…”
Section: Discussionmentioning
confidence: 99%